An electrostatic gate for mechanically controlled single-molecule junctions - Ballmann, Stefan Dieter; Weber, Heiko B. (New Journal of Physics, 2012)
We present a fabrication scheme for a tunable single-molecule transistor that allows for controlling the electrode separation and provides an electrostatic gate. The experimental approach is based on the mechanically controlled break junction technique but integrates an additional bottom gate electrode and an uninterrupted high-kappa gate dielectric. The device performance is demonstrated for a single-molecule junction showing Coulomb blockade characteristics.